Reutilization of chemical waste in methodologies for analyses of neutral detergent fiber and acid detergent fiber - doi: 10.4025/actascianimsci.v35i3.18591 - Lourenço, Maria do Socorro Nahuz; Berchielli, Telma Teresinha; Sader, Ana Paula de Oliveira; Malheiros, Euclides Braga; Messana, Juliana Duarte; Canesin, Roberta Carrilho (Acta Scientiarum. Animal Sciences, 2013)
The disposal of chemical waste and the precision of analyses of the neutral (NDF) and acid (ADF) detergent fiber contents were evaluated utilizing conventional (Van Soest) and alternative methods of analyses. The recovery of acetone promoted both economic and environmental gains, with a recovery rate of 84.12%. The precision of the analyses was not observed in most of the determinations with reutilization of chemical waste in all the analytical methods tested, in spite of promoting decrease in cost, time invested in the preparation of solutions and the disposal of chemical waste.